Evaluation Of Antenatal Checkup Practices Observed Among Beneficiaries & Non-Beneficiaries Under Janani Suraksha Yojana Scheme in Indore, India - Sharma, Shireen; Arora, V K; Shahjada, Ahmed; Mahashabde, Piyusha; Bachhotiya, Abhishek (National Journal of Community Medicine, 2014)
Introduction: Maternal mortality has been considered as a sign of social injustice to basic human health. GOI initiated some schemes to promote institutional deliveries with the ultimate objective of bringing down IMR and MMR one such scheme is Janani Suraksha Yojana under this scheme cash incentive is given to women opting for institutional delivery. Objective: To find out the utilization and association between services of ANC among Beneficiary and non- Beneficiary. Material & Method: A cross sectional study conducted over a period of one year, by using 30 clusters random sampling technique, with sample size of 450. Result: 69.5% was beneficiaries and 30.4% non-beneficiaries. 82.5% beneficiaries and 81.8% were found to be literate. Registration for ANC services, among beneficiary was found out to be 99.6% as compared to non-beneficiaries which was 97.8%. 74.4% beneficiaries had received 2tetanus and 72.8% had received more than 90 IFA tablets.